Tales that moved a nation a glimpse of literary journalism in the Philippines from 1972 to 2012 - Agustin, Jon Lindley Celestial; Cabujat, Myra A. (2013)
"Journalism is not just confined to informing the public. It also aims for the shaping of public opinion. Good journalism must be able to present stories effectively. Before even conventional news styles came into existence, the style of journalists then were narrative, descriptive and even persuasive with the articles in long form. This style is called literary journalism, started by Nick Joaquin in the Philippines. The researchers see the potential of literary journalism pieces on influencing public opinion. But challenges to its subsistence, i.e, shorter and more concise stories online journalism and the new media, have hampered its objective. This research was made in reference to an earlier UP CMC thesis on literary journalism from 1950s to 1980s, written by Dewey Joseph yap. He concluded in his study that literary journalism died as the 1980s drew to a close. Through interviews and content analysis, this research was able to establish the fact that literary journalism continued to flourish throughout the years. This research was able to explore the state of literary journalism after the 1986 EDSA People Power, exposing how literary journalism changed in scope and form, which reflects the social events in the in each decade we analyzed."